SAT-275 Bitemporal Hemianopia as a Result of Cabergoline Therapy for Macroprolactinoma - Díaz-Balzac, Carlos A (J Endocr Soc, 2020)
Background: Cabergoline is first-line treatment for prolactin-secreting pituitary macroadenoma (prolactinoma). Side effects such as nausea, valvulopathy and neuropsychiatric symptoms are well recognized complications of its use. A rare complication is vision loss secondary to empty-sella syndrome. Clinical case: A 27-years old women was diagnosed in 2009 with macroprolactinoma with a prolactin level of 2,523.91ng/mL (normal 3.3-26.7ng/mL), during work up of frontal headaches, amenorrhea and infertility. The rest of her pituitary work up was normal. She was started on dopamine receptor agonist therapy with Cabergoline 0.25mg two times a week. Her headaches improved within a few month. The prolactin level normalized and MRI at 1 year after starting Cabergoline therapy showed significant decrease in pituitary adenoma to 3mm. She continued Cabergoline therapy for 3 years, after which time it was discontinued. For the next 6-8 years she was on and off Cabergoline therapy for mild elevation of prolactin and galactorrhea/headache symptoms, with improvement of symptoms on Cabergoline. However, nine years after diagnosis and Cabergoline treatment, she developed vision loss, characterized by bitemporal hemianopia. MRI showed partial empty sella with downward displacement of the optic chiasm. Cabergoline therapy was stopped with some improvement of visual symptoms on exam. Here latest prolactin level is at 134ng/ml. Surgical management with chiasmapexy is being explored. Conclusion: Vision loss secondary to optic nerve traction from chiasmal herniation in the setting of an empty sella can be a consequence of Cabergoline therapy. No predictors or risk factors are known for the development of this complication. Furthermore, no clear evidence is available of benefit from discontinuation/continuation of therapy. Novel surgical management with chiasmapexy is being explored as a solution to stabilize the optic chiasm and resolve visual symptoms without further complications.